Efektivitas Manajemen Risiko Sumber Daya Manusia dalam Menghadapi Risiko Keamanan Data Karyawan di Sektor Teknologi - Ridho Alfi Fajar Hidayat; M. Rafli Lingga; Rushel Hardi; Abdul Haris Veriyadna; Arsyadona Arsyadona (Manajemen Kreatif Jurnal, 2024)
This research aims to explore the effectiveness of human resource risk management in dealing with employee data security risks in the technology sector. Given the increasing threats to information security, especially in today’s digital age, this research uses a qualitative approach with systematic literature analysis of various related articles and studies. The results show that the existence of clear security policies and procedures, regular employee training, the use of appropriate technology, and an organizational culture that supports information security are key factors that influence the effectiveness of risk management. In addition, evaluation and gathering feedback from employees are important elements in adjusting policies to meet evolving security challenges. This research provides recommendations for companies in the technology sector to improve their risk management systems through the integration of comprehensive policies, effective training programs, and the implementation of advanced technology, in order to protect employee data and increase trust within the organization.